Impact of FDI on economic growth from the sustainable development perspective: A case study from the assessment in the middle of Vietnam - Tien. N. N; Thuy.N.T.T; Binh. L.T.T (My University, 2020)
Impact of FDI on economic growth from the sustainable development perspective: A case study from the assessment in the middle of Vietnam
Keywords: FDI; Economic growth; Sustainable development